Absolute Lymphocyte Count: A Predictor of Recurrent Cytomegalovirus Disease in Solid Organ Transplant Recipients. (9th April 2018) - Gardiner, Bradley J; Nierenberg, Natalie E; Chow, Jennifer K; Ruthazer, Robin; Kent, David M; Snydman, David R
Abstract : In a retrospective cohort study of 170 solid organ transplant recipients who completed treatment for an episode of cytomegalovirus disease, absolute lymphocyte count within a week of cessation of primary treatment emerged as an independent predictor of relapse. Abstract: Background: Recurrent cytomegalovirus (CMV) disease in solid organ transplant recipients frequently occurs despite effective antiviral therapy. We previously demonstrated that patients with lymphopenia before liver transplantation are more likely to develop posttransplant infectious complications including CMV. The aim of this study was to explore absolute lymphocyte count (ALC) as a predictor of relapse following treatment for CMV disease. Methods: We performed a retrospective cohort study of heart, liver, and kidney transplant recipients treated for an episode of CMV disease. Our primary outcome was time to relapse of CMV within 6 months. Data on potential predictors of relapse including ALC were collected at the time of CMV treatment completion. Univariate and multivariate hazard ratios (HRs) were calculated with a Cox model. Multiple imputation was used to complete the data. Results: Relapse occurred in 33 of 170 participants (19.4%). Mean ALC in relapse-free patients was 1.08 ± 0.69 vs 0.73 ± 0.42 × 10 3 cells/μL in those who relapsed, corresponding to an unadjusted hazard ratio of 1.11 (95% confidence interval, 1.03–1.21; P = .009, n = 133) for every decrease of 100 cells/μL. After adjusting for potential confounders, the association between ALC and relapse remained significant (HR, 1.11 [1.03–1.20]; P = .009). Conclusions: Low ALC at the time of CMV treatment completion was a strong independent predictor for recurrent CMV disease. This finding is biologically plausible given the known importance of T-cell immunity in maintaining CMV latency. Future studies should consider this inexpensive, readily available marker of host immunity.